The Effect of Agility and Balance on Dribbling Speed of The Aisyah Pringsewu University Football Team - Armanjaya, Satria; Ahmad Nuruhidin; Ziko Fajar Ramadhan; Aditya Trinanda; Felinda Sari; Arif Alexander Bastian (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
Soccer is a team game, which is very popular with all Indonesians and even the world. Objectives: 1) Training methods between zig-zag run and t-drill in increasing dribbling speed, 2) Differences in high and low balance on increasing dribbling speed, 3) interaction between agility training methods with balance on increasing dribbling speed. This study uses an experimental method with a 2x2 factorial design. The independent variables in this study are zig-zag and t-drill running, high and low balance attribute variables, and the dependent variable is dribbling speed. The population is 36 players. The sampling technique used purposive sampling which amounted to 36 players. Data from the final test were analyzed with two-way ANOVA statistics. The results of calculations using SPSS 25 were obtained: 1) The first hypothesis obtained F count> Ftable or 86.532> 3.33 and a significance value of 0.000 <0.05. 2) The second hypothesis obtained F count> Ftable or 77,184> 3.33, and a significance value of 0.000 <0.05. 3) The third hypothesis obtained F count > Ftable or 9.615 > 3.33, and a significance value of 0.004 < 0.05. Conclusion: the group treated with the zig-zag run agility training method is better than the tdrill agility training group at dribbling speed. the group that has high balance is better than the group with low balance at dribbling speed. There is an interaction between agility training and balance level on dribbling speed.